Tinjauan Terhadap Hak Imunitas Komite Stabilitas Sistem Keuangan dalam Menanggulangi Pandemi Covid-19 - Ramur, Irham (UIN Sunan Kalijaga Yogyakarta, 2022)
Abstract: The massive spread of the Covid-19 virus has impacted various aspects, one of which is the economic factor. Because of this, the government has declared Indonesia to be in a state of non-natural emergency, for which reason it is necessary to make responsive and fast efforts to deal with this pandemic. The government grants immunity to the Financial System Stability Committee (KSSK) in exercising its authority to deal with the economic impact of Covid-19. This right of immunity has raised pros and cons so that a judicial review to the Constitutional Court. This paper will discuss the pros and cons regarding the immunity given to the KSSK and review whether the KSSK has succeeded in exercising its authority and prove whether the fear of being given immunity to the KSSK is proven or not. From various studies, it was concluded that KSSK's responsiveness in responding to every impact of Covid-19 needs to be appreciated. The policies that have been issued have succeeded in reducing the negative impact on economic growth in Indonesia. Although previously there was an institution responsible for overcoming the 1998 economic crisis, namely the Indonesian Bank Restructuring Agency (IBRA), which was also given great discretion. Even though IBRA ended up having problems in the BLBI case, so far the KSSK has not been proven to have abused its power.Abstrak: Masifnya penyebaran virus Covid-19 telah berdampak keberbagai aspek, salah satunya faktor ekonomi. Karenanya pemerintah telah menyatakan Indonesia dalam keadaan darurat non-alam, yang oleh karena hal tersebut perlu ada upaya tanggap, dan cepat untuk menanggulangi pandemi ini. Pemerintah memberikan imunitas kepada Komite Stabilitas Sistem Keuangan (KSSK) dalam melaksanakan kewenangannya untuk mengatasi dampak ekonomi oleh Covid-19. Hak imunitas tersebut telah menimbulkan pro-kontra sehingga juga telah dimohonkan judicial review ke Mahkamah Konstitusi. Tulisan ini akan membahas bagaimana pro-kontra terkait imunitas yang diberikan kepada KSSK dan meninjau apakah KSSK telah berhasil melaksanakan kewenangannya serta membuktikan apakah ketakutan dengan diberikan imunitas kepada KSSK terbukti atau tidak. Dari berbagai kajian, disimpulkan bahwa gerak tanggap KSSK dalam merespon setiap dampak dari Covid-19 perlu diapresisasi. Kebijakan-kebijakan yang telah dikeluarkan berhasil meredam dampak negatif terhadap pertumbuhan ekonomi di Indonesia. Kendatipun sebelumnya pernah ada lembaga yang bertanggungjawab untuk mengatasi krisis ekonomi tahun 1998 yaitu Badan Penyehatan Perbankan Nasional (BPPN) yang juga diberikan keleluasan besar. Meskipun BPPN berujung masalah dalam kasus BLBI, KSSK sampai saat ini belum tetbukti telah menggunak kewenagannya secara salah dan berlebihan (abuse of power).